2007
DOI: 10.1021/jo0624086
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Multicomponent Reactions for the Synthesis of N-Aryl Trisubstituted Pyrroles

Abstract: Dirhodium(II) salts efficiently catalyze the three-component assembly reaction of an imine, diazoacetonitrile (DAN), and an activated alkynyl coupling partner to form substituted 1,2-diarylpyrroles in moderate to good yields. The transition-metal-catalyzed decomposition of the diazo compound in the presence of the imine presumably generates a transient azomethine ylide that undergoes cycloaddition with dipolarophiles in a highly convergent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Several new direct pyrrole syntheses based on multicomponent reactions (Section 4.4.10) have emerged recently, featuring for instance imines, diazoacetonitrile, and alkynes as the reactants in the presence of a rhodium(II) catalyst. The sequence of events leading to pyrroles presumably involves initial decomposition of the diazo compound, formation of an intermediate azomethine ylide upon reaction with the imine, and finally cycloaddition with the alkyne [726]. Similar sets of starting compounds, namely, imines, acid chlorides, and alkynes, may also be converted into pyrroles in the presence of either isocyanides [727] or phosphines [728].…”
Section: Addendummentioning
confidence: 99%
“…Several new direct pyrrole syntheses based on multicomponent reactions (Section 4.4.10) have emerged recently, featuring for instance imines, diazoacetonitrile, and alkynes as the reactants in the presence of a rhodium(II) catalyst. The sequence of events leading to pyrroles presumably involves initial decomposition of the diazo compound, formation of an intermediate azomethine ylide upon reaction with the imine, and finally cycloaddition with the alkyne [726]. Similar sets of starting compounds, namely, imines, acid chlorides, and alkynes, may also be converted into pyrroles in the presence of either isocyanides [727] or phosphines [728].…”
Section: Addendummentioning
confidence: 99%
“…A subsequent 5-endo-dig cyclization afforded a variety of 1,2,3,5-tetrasubstituted and even 1,2-fused pyrroles in moderate to good yields. 8 In their recent study, Scheidt and coworkers devised the Rh(II)-catalyzed methodology employing imines, activated alkynes and diazoacetonitrile (DAN) in a convergent three-component 2 þ 2 þ 1 assembly reaction leading to pyrrolo-3,4-dicarboxylates 359 in moderate to high yields (Scheme 8.124) [317]. The authors proposed that DAN reacts with the Rh(II) catalyst to generate the corresponding metallocarbenoid 360.…”
Section: %mentioning
confidence: 99%
“…Additionally, a study showed that a Lewis acid can activate to cyclopropanes which react with aliphatic, aromatic, and á,â-unsaturated nitriles via dipolar cycloaddition [3 + 2], following by dehydration, and a tautomerization sequence for preparation of pyrroles 6 . Another report indicated that the Dirhodium(II) reagent can used in the threecomponent system (imine, diazoacetonitrile, and an activated alkynyl) as catalyst to form substituted 1,2-diarylpyrroles 7 .In addition, a study showed that Au(I) reagent Catalyzed the reaction of aryl-substituted with N-tosyl alkynyl aziridines to give 2,5-substituted pyrroles 8 . Another study showed a rearrangement reaction of a propargylic-aziridine, catalyzed by PPh 3 AuCl/AgOTf, forming some pyrrole derivatives 9 .…”
Section: Introductionmentioning
confidence: 99%